Measurements of the motions of atoms: flow velocities and diffusion constants - Prodan, John V., author; Fairbank, William M., Jr., advisor; She, Chiao-Yao, advisor (Colorado State University. Libraries, 1981)
Using Fluorescence Correlation Spectroscopy (FCS), the motion of atoms have been measured in real time. Single sodium atoms have been detected with this method and their flow velocity crudely measured. By averaging over many atoms, very clear signals were obtained and velocities up to 85 m/sec were measured. These velocities were determined by measuring the transit time of atoms across two resonantly tuned laser beams. Diffusion constants, D, of sodium in helium, neon and argon buffer gases were also measured using FCS. The products, Dp, where p is the pressure of the buffer gas, for these three cases were determined to be 427 ± 7 Torr cm2/sec, 277 ± 10 Torr cm2/sec and 200 ± 9 Torr cm2/sec, respectively. These numbers were obtained from measuring the average duration of the fluorescence burst from individual sodium atoms diffusing through the laser beam. Also measured was the diffusion constant for the excited sodium atom (2P3/2) in a helium buffer gas at 200 Torr pressure, with a result of 598 ± 84 Torr cm2/sec.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Atoms; Laser spectroscopy